Application of Job Design Strategy for Businesses MSMEs Facing the New Normal Era - Arief Dwi Saputra; Alfina Rahmatia; Andi Azhar; Rr. Sri Handari Wahyuningsih (Jurnal Manajemen Indonesia, 2022)
The process of determining an organization's purpose to achieve its goals using three approaches is known as job design, particularly job enlargement, job rotation, and job enrichment. This study aims to prove and see how job design can be used as a strategy in the new normal era of business to improve the quality of human resources. This study adopted mixed-method research with quantitative and qualitative approaches. Data was carried out through literature studies (reputable journals), questionnaires, and in-depth interviews through Zoom, Google Meet, and WhatsApp applications. Data processing is done by collecting data with purposive sampling of 164 respondents. The data is managed using SEM AMOS & Nvivo plus 12 applications. Furthermore, on task significance, skill variety, autonomy, feedback, and task identity, study the potential motivation index based on the Motivating Potential Score (MPS). Finally, an assessment was carried out with the Job Diagnostic Survey (JDS) to produce a potential motivation score, namely low, moderate, or high motivation. The findings of this study suggest that job design can be used as a business strategy in the face of the new normal era for improving the quality of human capital since there is a high motivation strengthening by job rotation, job enlargement, and job enrichment. It is strengthened by achieving job design on motivation that increases productivity, commitment, and satisfaction and reduces turnover intention, insecurity, and work stress. Keywords—Job Design; Motivating Potential Score (MPS); Job Diagnostic Survey (JDS); MSME Business; New Normal